Dynamical constraints on the dark matter distribution in the Milky Way - Pato, Miguel; Iocco, Fabio [UNESP]; Bertone, Gianfranco (IOP Publishing, 2015)
An accurate knowledge of the dark matter distribution in the Milky Way is of crucial importance for galaxy formation studies and current searches for particle dark matter. In this paper we set new dynamical constraints on the Galactic dark matter profile by comparing the observed rotation curve, updated with a comprehensive compilation of kinematic tracers, with that inferred from a wide range of observation-based morphologies of the bulge, disc and gas. The generalised Navarro-Frenk-White (NFW) and Einasto dark matter profiles are fitted to the data in order to determine the favoured ranges of local density, slope and scale radius. For a representative baryonic model, a typical local circular velocity v0=230 km/s and a distance of the Sun to the Galactic centre R0=8 kpc, we find a local dark matter density ρ0 = 0.420+0.021-0.018 (2σ) ± 0.025 GeV/cm3 (ρ0 = 0.420+0.019-0.021 (2σ) ± 0.026 GeV/cm3) for NFW (Einasto), where the second error is an estimate of the systematic due to baryonic modelling. Apart from the Galactic parameters, the main sources of uncertainty inside and outside the solar circle are baryonic modelling and rotation curve measurements, respectively. Upcoming astronomical observations are expected to reduce all these uncertainties substantially over the coming years.
Keywords: dark matter experiments; dark matter simulations; rotation curves of galaxies